Ethnomathematics of Gringsing Ikat Woven Fabrics in Tenganan Village: Study of Geometry Concepts in Lubeng Motifs (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
The purpose of this study is to determine: (1) the mathematical concepts contained in the Grisngsing Ikat Ikat in Tenganan Village with Lubeng motifs, and (2) the potential for its use in learning mathematics. This type of research is a qualitative research with an exploratory method that focuses on ethnomathematical studies. The main instrument in this study is the researcher himself who acts as an instrument as well as data collector. The results of the study from this research, namely: (1) The Gringsing Ikat Weaving Fabric with the Lubeng motif is a typical ikat cloth of Tenganan Village which in its motif contains mathematical concepts and concepts, such as the concept of transformation geometry in the form of reflection, translation, dilation, and rotation, as well as the concept of folding symmetry and rotary symmetry; and 2) the mathematical concepts contained in the Lubeng Ikat Ikat cloth can be integrated into the mathematics learning process for students in the Tenganan Village area, or students who know the culture of the Gringsing Ikat Weaving cloth as meaningful mathematics learning content.